2021
DOI: 10.1002/anie.202014196
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Palladium‐Catalyzed Deuterogenolysis of Carbon Oxygen Bonds towards Deuterated Pharmaceuticals

Abstract: Site‐specific incorporation of deuterium into drug molecules to study and improve their biological properties is crucial for drug discovery and development. Herein, we describe a palladium‐catalyzed room‐temperature deuterogenolysis of carbon–oxygen bonds in alcohols and ketones with D2 balloon for practical synthesis of deuterated pharmaceuticals and chemicals with benzyl‐site (sp3 C−H) D‐incorporation. The highlights of this deoxygenative deuteration strategy are mild conditions, broad scope, practicability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Among the numerous unsaturated bonds, alkynes (C≡C) are the most active in terms of reduction potential and can be readily semi-deuterated to d 2 -alkenes prior to water splitting. The conversion of semi-deuterated alkenes into fully deuterated alkanes is much more challenging due to their shortened bond lengths, which require a more negative potential [39] . The nitro functionality is Modified with permission from ref.…”
Section: Heavy Water Splitting As a Greener Option For Controllable Deuterationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the numerous unsaturated bonds, alkynes (C≡C) are the most active in terms of reduction potential and can be readily semi-deuterated to d 2 -alkenes prior to water splitting. The conversion of semi-deuterated alkenes into fully deuterated alkanes is much more challenging due to their shortened bond lengths, which require a more negative potential [39] . The nitro functionality is Modified with permission from ref.…”
Section: Heavy Water Splitting As a Greener Option For Controllable Deuterationmentioning
confidence: 99%
“…Substantial efforts have been devoted to regulating the catalytic activity by tailoring the electron structure and state of the d-band center through doping, alloying, defect and strain engineering. For instance, Wu et al [39] reported a phosphorus-doped palladium nanowire (Pd-P) cathode for selective semi-hydrogenation (deuteration) of terminal and internal alkynes using H 2 O(D 2 O) as the H(D) source. The CV pattern in neutral conditions displays a weakened H* adsorption after the addition of alkyne, indicating the competitive coverage of alkyne on the H* ads sites.…”
Section: Heavy Water Splitting As a Greener Option For Controllable Deuterationmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization data matched those previously reported. 39 Seeking to further disprove any potential mechanisms involving an alkene intermediate, we synthesized tetradeuterated d4-biphenyl ethanol (65) from bisdeuterated d2-biphenyl acetic acid methyl ester (S20) (prepared according to a literature procedure) 52 and subjected it to the general reaction conditions. We imagined that -if an alkene intermediate were present -then the Ni catalyst could be found on either carbon, leading to deuterium scrambling.…”
Section: Magnolol (57) Was Prepared From Bis-o-benzyl Magnolol According To Generalmentioning
confidence: 99%
“…[1,1'-Biphenyl]-4-d2-acetic acid methyl ester (S20) was prepared from [1,1'biphenyl]-4-glyoxylic acid methyl ester according to a literature procedure. 52 Column chromatography was performed using a gradient of 1→30% ethyl acetate in hexanes to afford (S20) as a colourless liquid (134 mg, 48% yield). Characterization data matched those previously reported.…”
Section: Figure S10 Deuteration Experiments Providing Evidence Against An Alkene Intermediatementioning
confidence: 99%